2015
DOI: 10.1063/1.4932177
|View full text |Cite
|
Sign up to set email alerts
|

On-chip DNA preconcentration in different media conductivities by electrodeless dielectrophoresis

Abstract: Electrodeless dielectrophoresis is the best choice to achieve preconcentration of nanoparticles and biomolecules due to its simple, robust, and easy implementation. We designed a simple chip with microchannels and nano-slits in between and then studied the trapping of DNA in high conductive medium and low conductive medium, corresponding to positive and negative dielectrophoresis (DEP), respectively. It is very important to investigate the trapping in media with different conductivities since one always has to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Moreover, Li et al. determined that the type of dielectrophoresis, that is, negative or positive dielectrophoresis, depends on the buffer conductivity , which is in good agreement to the theory (see Section ).…”
Section: Applicationssupporting
confidence: 56%
See 3 more Smart Citations
“…Moreover, Li et al. determined that the type of dielectrophoresis, that is, negative or positive dielectrophoresis, depends on the buffer conductivity , which is in good agreement to the theory (see Section ).…”
Section: Applicationssupporting
confidence: 56%
“…In 2015, Li et al. investigated DNA trapping behavior in nanoslits for different medium conductivities . They observed that the electrokinetic effects of electrophoresis, electroosmotic flow, and dielectrophoresis were affected by the buffer conductivity, similar to Regtmeier et al.…”
Section: Applicationsmentioning
confidence: 87%
See 2 more Smart Citations
“…Consequently, the realization of microfluidic platforms for the manipulation and analysis of biological and chemical samples has attracted significant interest in recent decades. [1][2][3][4] Human blood samples include many proteins with relevance to disease diagnosis and therapeutic monitoring. However, biochemical samples such as blood typically comprise many different components, including deoxyribonucleic acid (DNA), proteins, cells, and even ions.…”
Section: Introductionmentioning
confidence: 99%